2016
DOI: 10.1080/07420528.2016.1213739
|View full text |Cite
|
Sign up to set email alerts
|

Social jetlag affects subjective daytime sleepiness in school-aged children and adolescents: A study using the Japanese version of the Pediatric Daytime Sleepiness Scale (PDSS-J)

Abstract: The aim of this study was to elucidate the level of daytime sleepiness in Japanese school-aged children and adolescents, and to examine associated factors including sleep loss and social jetlag using the Japanese version of the Pediatric Daytime Sleepiness Scale (PDSS-J). After the linguistic validation of the PDSS-J with a multi-step translation methodology, consisting of forward translation, back translation, expert review and cognitive debriefing interviews, we conducted a psychometric validation for 492 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 33 publications
6
29
1
3
Order By: Relevance
“…In the current study, more than a quarter (26.5% (561/2114)) of whole students were categorized into SJL 4 and 5, who had a SJL of more than 1 hours. SJL [9] has been paid attention recently and is known to be associated with variable problems [36][37][38][39], especially among those who had a SJL of more than 1 hour [37]. Consistently, the current study revealed that the mean self-reported AP of SJL 3 was better than that of SJL 4 and 5 (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, more than a quarter (26.5% (561/2114)) of whole students were categorized into SJL 4 and 5, who had a SJL of more than 1 hours. SJL [9] has been paid attention recently and is known to be associated with variable problems [36][37][38][39], especially among those who had a SJL of more than 1 hour [37]. Consistently, the current study revealed that the mean self-reported AP of SJL 3 was better than that of SJL 4 and 5 (Figure 1).…”
Section: Discussionsupporting
confidence: 85%
“…The PDSS is designed to assess sleepiness in 11–15‐year‐old students (Cronbach's α = 0.796). In addition, there are several studies utilising PDSS on older adolescents aged 16 and 17 . Items related to daytime sleepiness are scaled from 0 (never) to 4 (always).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are several studies utilising PDSS on older adolescents aged 16 and 17. 24,25 Items related to daytime sleepiness are scaled from 0 (never) to 4 (always). Item scores are summed to produce a total score, with item 3 being reverse scored.…”
Section: Assessmentmentioning
confidence: 99%
“…The Cronbach's alpha of the scale in our sample was 0.80. The discriminative validity of the Chinese version [60] and the factorial validity and concurrent validity of the Japanese version [61] were acceptable. The correlation coefficient of test-retest reliability of the Chinese version was 0.78 [60] which was satisfactory.…”
Section: Measurementmentioning
confidence: 90%
“…The correlation coefficient of test-retest reliability of the Chinese version was 0.78 [60] which was satisfactory. The intra-class correlation coefficient of intra-rater reliability of the Japanese version was 0.88 [61].…”
Section: Measurementmentioning
confidence: 93%